PENGARUH PEMBERIAN PENGUATAN POSITIFDAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATEMATIKASISWA KELAS IV SD SE-KECAMATAN KLIRONG - pgsd, amanah (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Effect of the Giving Positive Reinforcement and Learning Interest in Mathematic Learning Result ofFourth Grade Student Elementary School in Klirong District.The purpose of this research are find out: (1) the effect of different giving positive reinforcement in Mathematic learning result of the fourth grade student elementary school in Klirong District, (2) the effect of different learning interest in Mathematic learning result of the fourth grade student elementary school in Klirong District; (3) the effect of interaction between giving positive reinforcement and learning interest in Mathematic learning result of the fourth grade student elementary school in Klirong District. This method uses is an experimental method with a quantitative research. The result research can be concluded that: (1) giving positive reinforcement effect in Mathematic learning result of the fourth grade student elementary school in Klirong District, (2)learning interest effect in Mathematic learning result of the fourth grade student elementary school in Klirong District; (3) giving positive reinforcement interact with learning interest effect in Mathematic learning result of the fourth grade student elementary school in Klirong District. Keywords: giving positive reinforcement, learning interest, learning result,Mathematic Abstrak: Pengaruh Pemberian Penguatan Positif dan Minat Belajar terhadap Hasil Belajar Matematika Siswa Kelas IV SD se-Kecamatan Klirong.Tujuan penelitianadalah untuk membuktikan:(1) pengaruh perbedaan pemberian penguatan positif terhadap hasil belajar Matematika siswa kelas IV SD se-Kecamatan Klirong; (2) pengaruh perbedaan minat belajar terhadap hasil belajar Matematika siswa kelas IV SD se-Kecamatan Klirong; (3) pengaruh interaksi antara pemberian penguatan positif dan minat belajar terhadap hasil belajar Matematika siswa kelas IV SD se-Kecamatan Klirong. Penelitian ini menggunakan metode eksperimental dengan pendekatan penelitian kuantitatif. Hasil penelitian dapat disimpulkan bahwa: (1) pemberian penguatan positif berpengaruh terhadap hasil belajar Matematika siswa kelas IV SD se-Kecamatan Klirong; (2) minat belajar berpengaruh terhadap hasil belajar Matematika siswa kelas IV SD se-Kecamatan Klirong; (3) pemberian penguatan positif berinteraksi dengan minat belajar berpengaruh terhadap hasil belajar Matematika siswa kelas IV SD se-Kecamatan Klirong tahun ajaran 2012/2013.   Kata kunci: pemberian penguatan positif, minat belajar, hasil belajar, Matematika